2015
DOI: 10.1016/j.jmgm.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chikungunya virus nsP2 protease inhibitors using structure-base approaches

Abstract: . (2015). Identification of chikungunya virus nsP2 protease inhibitors using structure-base approaches. Journal of Molecular Graphics and Modelling, 57 1-8. Identification of chikungunya virus nsP2 protease inhibitors using structure-base approaches AbstractThe nsP2 protease of chikungunya virus (CHIKV) is one of the essential components of viral replication and it plays a crucial role in the cleavage of polyprotein precursors for the viral replication process. Therefore, it is gaining attention as a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 41 publications
0
35
0
2
Order By: Relevance
“…Similarly, several potential inhibitors were identified using a combination of molecular docking, virtual screening, and molecular dynamics simulations on the crystal structure of CHIKV nsP2 protease (31). The best compounds were characterized by binding free energies up toϪ10.6 kcal/mol.…”
Section: -Fluoro-n-[2-(2-imidazol-1-yletoxy)phenyl]-1h-indol-2-carbomentioning
confidence: 99%
“…Similarly, several potential inhibitors were identified using a combination of molecular docking, virtual screening, and molecular dynamics simulations on the crystal structure of CHIKV nsP2 protease (31). The best compounds were characterized by binding free energies up toϪ10.6 kcal/mol.…”
Section: -Fluoro-n-[2-(2-imidazol-1-yletoxy)phenyl]-1h-indol-2-carbomentioning
confidence: 99%
“…To find out a few potential inhibitors against CHIKV nsp2 protease, homology modeling and computer-aided drug design strategies have been implemented for the first time (Bassetto et al, 2013). Potential inhibitors based on structural studies and molecular simulations have been reported (Nguyen et al, 2015;Singh et al, 2012).…”
Section: Viral Target Proteins For Drug Developmentmentioning
confidence: 99%
“…Penelitian tentang pencarian sisi aktif protease nsP2 dari virus chikungunya telah banyak dilakukan. Pocket 4 pada N-terminal protease nsP2 diidentifikasi sebagai sisi aktif yang potensial untuk dijadikan target inhibisi oleh suatu inhibitor dengan adanya residu katalitik Cys1013 dan His1083 (Nguyen, et al, 2015). Residu-residu asam amino Cys1013, Trp1014, Ala1046, Tyr1047, Ser1048, Tyr1084, Asn1082, Leu1205, Gly1206, Mse1238, Gln1241, Mse1242, dan Asp1246 menunjukkan interaksi yang krusial dengan protease nsP2 (Agarwal, et al, 2015).…”
Section: Pendahuluanunclassified
“…Hasil visualisasi dengan software Edu PyMOL, ligan kelompok flavonoid yang digunakan berada dalam satu sisi pengikatan yang sama dengan ligan kontrol pada penelitian Nguyen, et al tahun 2015. Ligan kontrol berada pada pocket 4 yang berisi residu-residu asam amino, yaitu Cys1013, Ala1046, Tyr1047, Ser1048, Pro1049, Glu1050, Val1051, Tyr1078, Tyr1079, Asn1082, His1083, Trp1084, Gly1090, Lys1091, Phe1093, Tyr1201, Asn1202, Glu1204, Leu1205, Gly1206, Pro1208, Ala1209, Met1238, Gln1241, Met1242, Gly1245, Asp1246 dan Arg1249 (Nguyen, et al, 2015). Berikut ini merupakan data residu asam amino yang berikatan langsung dengan ligan golongan flavonoid yang disajikan pada Tabel 4.…”
Section: Visualisasi Molekulunclassified